Adab, Hukum, Dan Tata Kelola Masyarakat: Transformasi Praktik Fikih Pada Era Umayyah Hingga Abbasiyah - Hendra Setiawan Maulana; Rina Kusumawati; Ahmad Yasin (CV JK Riset Publishing Group, 2026)
This study examines the transformation of fiqh (Islamic jurisprudence) practice in the domains of adab (ethics), law, and social governance from the Umayyad (661-750 CE) to the Abbasid (750-1258 CE) era. The research aims to analyze how Islamic legal thought evolved from a relatively informal tradition of scholarly opinion into a highly systematized body of jurisprudence with profound implications for state governance and social organization. Employing a qualitative historical-juridical approach with library research design and comparative legal analysis, this study draws on classical fiqh texts, historiographical sources, and contemporary Indonesian Islamic legal scholarship. Findings reveal three interconnected transformations: first, the institutionalization of qadi (judicial) courts and the professionalization of Islamic legal practice; second, the codification of adab as both ethical norm and jurisprudential category shaping governance; third, the emergence of the four major legal schools (madhahib) as pillars of social order and civilizational identity. This study concludes that the Umayyad-Abbasid transformation of fiqh represents a foundational chapter for understanding Islamic legal pluralism and its contemporary relevance for Indonesia.